2012
DOI: 10.5897/jdae11.053
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of migration and remittances in rural Nigeria

Abstract: This study uses NLSS, 2004 data collected for rural Nigeria to estimate a multinomial logit model of the economic and demographic determinants of migration and receipt of remittances in rural Nigeria. Findings showed that most of the human capital variables are statistically insignificant. However, for internal remittances, households with more educated members at the secondary school level (X 2), age of household head (X 4), Number of males over age 15 (X 7), zone 1, 2, 3 and 5, Land size (X 11), are positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…In the literature, migration is conceptualized as a life-cycle event (Görlich and Trebesch 2008;Olowa and Awoyemi 2012): Households headed by older persons are expected to have fewer dependent children but more family members in the working age group. Thus, the household head's age was reported as having a positive effect on migration in Guatemala (Adams 2006).…”
Section: Results Contributing To the Discussion Of Ambiguous Migratiomentioning
confidence: 99%
See 2 more Smart Citations
“…In the literature, migration is conceptualized as a life-cycle event (Görlich and Trebesch 2008;Olowa and Awoyemi 2012): Households headed by older persons are expected to have fewer dependent children but more family members in the working age group. Thus, the household head's age was reported as having a positive effect on migration in Guatemala (Adams 2006).…”
Section: Results Contributing To the Discussion Of Ambiguous Migratiomentioning
confidence: 99%
“…Bilsborrow (2002) also emphasises that places' different economic opportunities and the contextual factors of households influence peoples' migration decisions. As location seems to matter, and as only a few previous migration studies have included the contextual factor of household location (Taylor 1999;Ezra and Kiros 2001;Olowa and Awoyemi 2012), future empirical migration studies might be well advised to extend the NELM framework with locational meso-level variables in a multilevel analysis, particularly if they include short-term migration.…”
Section: Results Supplementing the Nelm Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…() found that households with more land are likely to be more capital‐constrained in crop production, thus more likely to seek income from migration in North China. Olowa and Awoyemi's () findings showed that land size is positively and significantly associated with internal migration in Nigeria, with a 1 ha increase of land size increasing the probability of internal migration by 0.32%.…”
Section: Land Tenure Arrangements and Migration In Chinamentioning
confidence: 98%
“…Brixiova and Ncube (2013). However, to our knowledge, no research work has tried answering this question except for the work of Olowa and Awoyemi (2012), that sort answers in terms of rural migration and remittances in Nigeria. This gap is the motivation for this study.…”
Section: Review Of Relevant Literaturementioning
confidence: 99%